Pengembangan Sistem Informasi Pengelolaan Jalan Desa Di Kabupaten Kapuas Hulu - Juniardi, Ferry; Azwansyah, Heri (Faculty of Engineering, Universitas Tanjungpura, 2015)
Abstractâ€“ This research aim to develop information system management of countryside road in Kapuas Hulu. This study requires countryside roads data obtained from relevant agencies, field surveys and various reference sources. The study resulted a geographical information system management of countryside road in Kapuas Hulu. This system can give information countryside road pursuant to condition of road, and street function, and can show of countryside road pursuant to name of district, and equiped by program information conservancy of countryside road. Keywordsâ€“ Countryside Rood, Geographical InformastionÂ System. Program Information Conservanc.